ISLAMIC INTERVENTION PROGRAM MODEL REDUCTION OF BULYYING BEHAVIOR AT SENIOR HIGH SCHOOLS PEKANBARU - Zaitun Zaitun (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This study aims to determine the cause of frequent violence in the education and to find behaviour typology leading to bullying that often occur at school and produce appropriate Islamic intervention program model for bullying. This study uses research and development that only focused on hypothetical phase. Writer collects data from several existing Senior High School in Pekanbaru-Riau. Data collection techniques use questionnaire, observation, interview and documentation. To obtain valid data, the researcher also conducted triangulation. The study concluded that intervention model can be done by streamline the peer coaching, religious mentoring intensively periodically that conducted school with involving counselling and religious teachers and maximize co-operation between parents, teachers and schools to make effective group counselling, mediation and use of ICT in the learning process.